Three-dimensional scanning in women with large, ptotic breasts: implications for bra cup sizing and design. Issue 3 (4th March 2017) - Coltman, Celeste E.; McGhee, Deirdre E.; Steele, Julie R.
Abstract: Background : This study aimed to compare breast volume calculated from scanning large, ptotic breasts of women while they were standing upright relative to when lying prone in order to identify the error associated with breast volume calculations.Methods : Breast volume and visualisation were compared in 50 women with large breasts (D + bra cup size) while they were scanned in three different positions.Results : Full visualisation of both breasts occurred in 100% of participants in the prone position and only 5% of participants in either standing position. Breast volume was significantly greater ( p < 0.01) in the prone position, with the percentage of underestimation in the standing position increasing as breast volume increased.Conclusion : Breast volume measured by three-dimensional scanning in the standing position will be underestimated by 7–10% in large, ptotic breasts. Consideration of these inaccuracies in breast volume relative to breast size can assist bra manufacturers when designing bras. Practitioner Summary : Errors have been reported when measuring the breast volume of women with large, ptotic breasts using three-dimensional scanning. This original research provides evidence for bra designers and manufacturers on the degree of error associated with this measurement. These errors should be accounted for in future bra designs.